Antioxidant activity of roots, stems, and leaves Spatholobus littoralis Hassk.: an experimental study - Ariesanti, Yessy; Wahyudina, Salsa Putri; Poedjiastoeti, Wiwiek; Angraini, Yenni (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: Tooth extraction is an action that will leave scars where the procedure is conducted. Post-extraction wounds will heal after going through 4 complex healing phases. Reactive Oxygen Species (ROS) play a role in wound healing, where antioxidants become substances that can control ROS levels in the body. Spatholobus littoralis Hassk., which comes from Central Kalimantan, has benefits in the wound healing phase. The aim of study was to analyze the effectiveness of Spatholobus littoralis Hassk., extracts on antioxidant activity. Methods: The type of research was an in vitro laboratory experimental study. Extracts of roots, stems, and leaves of Spatholobus littoralis Hassk. DPPH 2, 2-Diphenyl-1-picrylhydrazylradical as negative control, and Vitamin C as positive control were tested for antioxidants by using DPPH solution. Tests using a spectrophotometer with a wavelength of 517 nm were conducted after each sample was incubated for 30 minutes. Then, It would be calculated to determine the percentage of inhibition and IC50 of each sample. Data analysis used in this research was One-way ANOVA. Results: One-way ANOVA test showed no significant differences in the root extract, DPPH, and vitamin C groups; besides, there were significant differences in the stem and leaf extract groups. In the post hoc Tukey test, a concentration of 2500 ppm in stem extract was the most effective concentration, and a concentration of 2000 ppm in leaf extract was the most effective, with IC50 values from lowest to highest: stem extract (9.46), vitamin C (11.52), root extract (23.86), leaf extract (47.71), and DPPH (1660710) Conclusion: Extract of Spatholobus littoralis Hassk. has antioxidant activity, with the highest antioxidant activity in Spatholobus littoralis Hassk. stem extract, the most effective concentration is at 2500 ppm.Keywords: DPPH, reactive oxygen species, spatholobus littoralis Hassk.